Influence of Gypsum Amendment on Methane Emission from Paddy Soil Affected by Saline Irrigation Water - Theint, Ei E.; Bellingrath-Kimura, Sonoko D.; Oo, Aung Z.; Motobayashi, Takashi (Frontiers in Environmental Science, 2016)
To investigate the influence of gypsum application on methane (CH4) emission from paddy rice soil affected by saline irrigation water, two pot experiments with the rice cultivation were conducted. In pot experiment (I), salinity levels 30 mMNaCl (S30) and 90 mMNaCl (S90), that showed maximum and minimum CH4 production in an incubation experiment, respectively, were selected and studied without and with application of 1 Mg gypsum ha−1(G1). In pot Experiment (II), CH4 emission was investigated under different rates of gypsum application: 1 (G1), 2.5 (G2.5), and 5 (G5) Mg gypsum ha−1 under a non-saline and saline condition of 25 mMNaCl (S25). In Experiment (I), the smallest CH4 emission was observed in S90. Methane emission in S30 was not significantly different with the non-saline control. The addition of gypsum showed significant lower CH4 emission in saline and non-saline treatments compared with non-saline control. In Experiment (II), the CH4 emissions in the saline treatments were not significantly different to the non-saline treatments except S25-G5. However, our work has shown that gypsum can lower CH4 emissions under saline and non-saline conditions. Thus, gypsum can be used as a CH4 mitigation option in non-saline as well as in saline conditions.